Pemanfaatan Infrastruktur Jembatan Ngujang II Di Sungai Brantas Sebagai Dominasi Ekonomi Masyarakat - Chusnul Chotimah; Denis Nuranisa Ikhsani; Anggoro Putranto (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This research relates to the utilization of the infrastructure of the Ngujang II bridge on the Brantas river as the economic dominance of the community. This study uses a qualitative method, emphasizing the method of analysis, observation and interviews, data analysis is grouped from various sources, with the theory of economic development from Joseph Schumpeter. The results showed that in two different locations on the Ngujang II bridge, namely in the north a coffee shop and karaoke while in the south angkringan and a coffee shop. There are traders on the Ngujang II bridge who make this business their main livelihood and some only as a side because their main job as farmers.